Genealogy, Symbolic Capital, and Power Reproduction in the Bani Qomaruddin Pesantren Community - Wajdi, Ahmad Farid; Khabibullah, Muttaqin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Genealogical documentation has long been a central tradition in Javanese pesantren communities, serving not only to trace lineage but also to preserve spiritual authority and cultural continuity. In Bani Qomaruddin, genealogy plays a significant role in shaping social relations, moral legitimacy, and institutional leadership. This research aims to examine how genealogical practice is capitalized as symbolic capital in socio-religious, economic, and political domains. Using a qualitative case study approach, data were collected through in-depth interviews with key figures across sub-lineages, selected via purposive and snowball sampling. The data were analyzed using Miles, Huberman, and Saldaña’s interactive model, with Bourdieu’s theory of capital and field serving as the theoretical framework. Findings show that genealogy in Bani Qomaruddin operates as a dynamic field where various forms of capital—social, symbolic, economic, and political—are produced, converted, and contested. It also reveals that genealogical legitimacy functions as both a spiritual ethos and a mechanism for structuring authority and resource distribution. The implication of this study is that genealogical practice serves as a key instrument in the reproduction of power, solidarity, and identity within Indonesian Muslim society. Tradisi pencatatan silsilah telah lama menjadi bagian penting dalam masyarakat pesantren Jawa, tidak hanya untuk melacak garis keturunan, tetapi juga menjaga otoritas spiritual dan kesinambungan budaya. Di komunitas Bani Qomaruddin, praktik genealogis berperan besar dalam membentuk hubungan sosial, legitimasi moral, dan kepemimpinan kelembagaan. Penelitian ini bertujuan untuk mengkaji bagaimana praktik genealogis dikapitalisasi sebagai modal simbolik dalam ranah sosial-religius, ekonomi, dan politik. Penelitian ini menggunakan pendekatan kualitatif studi kasus, dengan teknik pengumpulan data melalui wawancara mendalam terhadap tokoh-tokoh kunci yang dipilih dengan teknik purposive dan snowball sampling. Data dianalisis dengan model interaktif Miles, Huberman, dan Saldaña, dan menggunakan teori modal dan ranah dari Pierre Bourdieu sebagai kerangka teoritik. Hasil penelitian menunjukkan bahwa genealogis di Bani Qomaruddin merupakan arena dinamis tempat berbagai bentuk modal diproduksi, dikonversi, dan diperebutkan. Legitimasi genealogis juga berfungsi sebagai etos spiritual sekaligus mekanisme dalam pengelolaan otoritas dan distribusi sumber daya. Implikasi dari penelitian ini adalah bahwa praktik genealogis menjadi instrumen penting dalam reproduksi kekuasaan, solidaritas, dan identitas dalam masyarakat Muslim Indonesia.